2002
DOI: 10.1002/jmv.10288
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐subtype cross‐neutralizing antibodies recognize epitopes on cell‐associated HIV‐1 virions

Abstract: HIV-1 infected individuals with cross-neutralizing antibodies against primary HIV-1 isolates belonging to Group M (envA-H) and O, are identified. To investigate the neutralization-kinetics of primary isolates with these antibodies, different neutralization assay conditions are compared. Each set is summarized as a/b/c where a is the time in hours for which antibody is incubated with virus, b is the time in hours allowed for virus to absorb to cells, c is the total culture period in days, from the cells' first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The results from the present and previous studies [10], [17], [18] indicate that multiple steps are involved in HIV-1 neutralization so that the virus-antibody complex remains infectious. Antibody binds to the free virion since neutralization increases as the incubation phase is extended.…”
Section: Discussionsupporting
confidence: 68%
“…The results from the present and previous studies [10], [17], [18] indicate that multiple steps are involved in HIV-1 neutralization so that the virus-antibody complex remains infectious. Antibody binds to the free virion since neutralization increases as the incubation phase is extended.…”
Section: Discussionsupporting
confidence: 68%
“…This index quantifies, by definition, a loss in virus infectivity: it does not matter how much antigen a single infectious dose of virus releases into the culture supernatant as long as this is enough to be registered as significant in an antigen capture ELISA. The culture phase has been extended to 14 days since previous experience has shown that a single infectious dose of virus can be detected after this interval in PBMC cultures even if its replication has been slowed down after exposure to HIV-1 seropositive plasma [Donners et al, 2003a]. In order to detect antibodies binding to the outside of the virion, the incubation phase of the assay has been extended.…”
Section: Discussionmentioning
confidence: 98%
“…The format of a traditional neutralization assay (e.g., 1/2/7) is based on the assumption that antibody binds to a virion when both are suspended in fluid. For primary isolates of HIV, this assumption may not be valid [Spenlehauer et al, 2001;Donners et al, 2003a]. Neutralization with primary HIV isolates may continue, and may only start, after the virus has bound to its target cell.…”
Section: Neutralization With Panel X Plasmamentioning
confidence: 94%
See 2 more Smart Citations